System with Thermal Management for Synergistic Water Production, Electricity Generation and Crop Irrigation - Wang, Meng; He, Zixiang; Chang, Haixing; Wei, Yen; Zhang, Shiyu; Wang, Ke; Xie, Peng; Wang, Rupeng; Ren, Nanqi; Ho, Shih‑Hsin (Nano-Micro Letters, 2025)
Sustainable water, energy and food (WEF) supplies are the bedrock upon which human society depends. Solar-driven interfacial evaporation, combined with electricity generation and cultivation, is a promising approach to mitigate the freshwater, energy and food crises. However, the performance of solar-driven systems decreases significantly during operation due to uncontrollable weather. This study proposes an integrated water/electricity cogeneration–cultivation system with superior thermal management. The energy storage evaporator, consisting of energy storage microcapsules/hydrogel composites, is optimally designed for sustainable desalination, achieving an evaporation rate of around 1.91 kg m−2 h−1. In the dark, heat released from the phase-change layer supported an evaporation rate of around 0.54 kg m−2 h−1. Reverse electrodialysis harnessed the salinity-gradient energy enhanced during desalination, enabling the long-running WEC system to achieve a power output of 0.3 W m−2, which was almost three times higher than that of conventional seawater/surface water mixing. Additionally, an integrated crop irrigation platform utilized system drainage for real-time, on-demand wheat cultivation without secondary contaminants, facilitating seamless WEF integration. This work presents a novel approach to all-day solar water production, electricity generation and crop irrigation, offering a solution and blueprint for the sustainable development of WEF. Highlights: 1 Dynamic thermal management: the system achieves evaporation rates of 1.91 kg m−2 h−1 (1 sun) and 0.54 kg m−2 h−1 (darkness) through energy storage hydrogel-based energy storage evaporator, effectively mitigating intermittent solar availability. 2 Enhanced salinity gradient utilization: integrated reverse electrodialysis (RED) system harvests 0.30 W m−2 from desalination-concentrated brine, tripling the output of conventional seawater/surface water RED system. 3 Sustainable resource integration: drainage water enables zero-pollution crop irrigation (shoot length 87 mm, 7 d), completing the seamless integration of water-energy-food nexus.